Új kihívások a középszintű államigazgatásban 2016-tól napjainkig A területi kormányhivatalok és járások továbbfejlesztésének főbb lépései és iránya - Barta, Attila; Jakab, Viktória (Debreceni Jogi Műhely, 2017)
This paper deals with the alteration of sub-national representation of government. Nowadays in Hungary the aforementioned institutions are called county (capital) government offices. The overview gives rise to the following research questions:Who are these representatives and what is the role of territorial government offices?Why interesting the Hungarian administrative improvement?What the future holds?The study concludes that the Hungarian Government has a comprehensive plan on the development of public administration until 2020, and the government offices and their districts play a pivotal role in this plan.